solve for x
5x + 3(x - 2) = -2(x + 1)

5x + 3(x - 2) = -2(x + 1) is equal to: x=2/5
Solution:
Solve for x:
3 (x-2)+5 x = -2 (x+1)
Distribute 3 over x-2.
3 (x-2) = 3 x-6:
3 x-6+5 x = -2 (x+1)
Add like terms in 5 x+3 x-6.
3 x+5 x = 8 x:
8 x-6 = -2 (x+1)
Write the linear polynomial on the [ left hand side in standard form.
Expand out terms of the right hand side:
8 x-6 = -2-2 x
Move terms with x to the left hand side.
Add 2 x to both sides:
8 x+2 x-6 = (2 x-2 x)-2
Look for two terms that sum to zero.
2 x-2 x = 0:
8 x+2 x-6 = -2
Add like terms in 8 x+2 x-6.
8 x+2 x = 10 x:
10 x-6 = -2
Isolate terms with x to the left hand side.
Add

6 to both sides:
10 x+(6-6) = 6-2
Look for two terms that sum to zero.
6-6 = 0:
10 x = 6-2
Evaluate 6-2.
6-2 = 4:
10 x = 4
Solve for x.
Divide both sides of 10 x = 4 by 10:
(10 x)/10 = 4/10
Any nonzero number divided by itself is one.
10/10 = 1:
x = 4/10
Reduce 4/10 to lowest terms.
The gcd of 4 and 10 is 2, so 4/10 = (2×2)/(2×5) = 2/2×2/5 = 2/5:
Answer: |
| x = 2/5
]

Expert answered|emdjay23|Points 1576|

Question

Asked 6/2/2013 11:47:26 AM

Updated 6/12/2014 2:02:48 PM

1 Answer/Comment

Rating

3

5x + 3(x - 2) = -2(x + 1);

5x + 3x - 6 = -2x - 2;

8x - 6 = -2x - 2;

8x + 2x = -2 + 6;

10x = 4;

x = 4/10;

x = 2/5

5x + 3x - 6 = -2x - 2;

8x - 6 = -2x - 2;

8x + 2x = -2 + 6;

10x = 4;

x = 4/10;

x = 2/5

Added 6/12/2014 2:02:48 PM

This answer has been confirmed as correct and helpful.

27,368,710

questions answered

There are no comments.